Enhancing Compressed Earth Block Performance: Effects of Gelatinized Starch and Fiber Reinforcement on Mechanical Properties - Gabo Cyprien Bailly; Yassine El Mendili; Athanas Konin; Eliane Khoury (Journal of Building Materials and Structures)
This study investigates the impact of starch stabilization and fiber reinforcement on the mechanical properties of Compressed Earth Blocks (CEBs). Various stabilization methods were tested to enhance the mechanical performance of CEBs, with a focus on starch as a natural binder and the incorporation of hemp as natural fibers. The research findings indicate that while starch slightly reduced internal cohesion by 13%, the addition of fibers alone significantly improved compression resistance by increasing strength by a factor of 3.57. When combined with starch, the effectiveness of fibers on compression resistance slightly decreased to a factor of 3.21. Cement stabilization, though providing the highest strength with a factor of 7, poses greater environmental challenges due to its high energy consumption and carbon emissions. In contrast, starch and natural fibers offer promising, eco-friendly alternatives that enhance CEB performance while reducing environmental impact. This study highlights the potential for integrating sustainable materials into construction practices to meet both structural and environmental objectives.